An analysis of the basic needs approach in its application to regional economic development with specific reference to Ciske - Keeton, Gavin Rodney (Rhodes University, Faculty of Commerce, Department of Economics, 2026)
In Chapter 7, it was argued that improved satisfaction of basic needs could in principle lead to increased labour productivity and, via a comulative process, to increased output and income levels. Higher incomes could in turn mean further improved satisfaction of basic needs, greater labour productivity and even greater output and income levels. Thus the satisfaction of basic needs could be seen as a means towards the end of improved living standards and the reduction of poverty, and hence an instrument of development policy. From the analysis of basic needs in Ciskei, it is apparent that government expenditure has been such that the "core" basic needs have evidently been catered for, at least to some extent, for some time. Yet, there has been nothing like a concerted strategy, and expenditure on basic needs was the result of ad hoc measures, rather than a conscious strategy or development policy as such. Basic needs were therefore seen simply as ends in themselves, rather than as means to the end of self-sustained economic development. In the case of Ciskei, more information about the satisfaction of basic needs, especially health, and water supply and sanitation, is required at the present stage. Such information should not only be seen in quantitative terms (as "inputs"), but also be evaluated qualitatively (as "outputs"). In other words, basic needs should be viewed functionally as thresholds to the goal of self-sustained economic development. This applies particularly to educatfon, where the total supply may be misleading, more significant measures being quality, access and actual consumption. Data for health, and water supply and sanitation, are not readily available, and again should reflect access and usage as well as availability. Nutritional data should not only reveal the extent and nature of poor nutrition (malnutrition) but also its causes, such as, inadequate expenditure on food on account of low income levels, or inappropriate nutritional patterns of consumption. Data on shelter should take into account the appropriateness of standards and types of shelter, rather than simply the number of houses as such. At the same time, the extent to which basic needs are complementary should be investigated
Keywords: Basic needs -- South Africa -- Ciskei; Ciskei (South Africa) -- Economic conditions; Ciskei (South Africa) -- Social conditions